Electromigration Effects in Overcurrent PVC-Insulated Copper Wire: Failure and Deformation Impacts - Akbar, Muhammad Ali; Tarigan, Kerista; Humaidi, Syahrul; Ramdan, Dadan; Siregar, Yulianta (Science and Technology Indonesia, 2024)
Electromigration is a critical issue in materials science and electrical engineering, significantly impacting the reliability and efficiency of electrical systems. This study investigates the electromigration behavior of PVC-insulated copper wires under various overcurrent conditions, focusing on material degradation and electrical performance. Copper cables, identified as 046620.3 Eterna CU/PVC 1.5 mm2, were subjected to currents ranging from 0 to 110 A. The mean time to failure (MTTF) was calculated using Black’s equation, revealing a sharp decline in MTTF with increasing current density. Surface morphology analysis using SEM showed the formation of voids and hillocks at higher currents, indicating severe electromigration damage. XRF analysis demonstrated significant changes in the elemental composition, particularly a reduction in copper content and an increase in chlorine and other elements, suggesting degradation of the PVC insulation. FTIR spectroscopy revealed substantial chemical changes in the PVC material, especially under extreme overcurrent conditions, highlighting dehydrochlorination and carbonyl group formation. There is a clear relationship between overcurrent conditions and electromigration phenomena, as evidenced by the observed damage to surface morphology, changes in elemental composition, and alterations in the chemical structure of PVC. The mechanisms and causes of electromigration are explained comprehensively in this work, illustrating how increased overcurrent accelerates the electromigration process, leading to the formation of voids and hillocks in the copper conductor. This damage is accompanied by a significant reduction in copper content and an increase in chlorine levels, indicating the degradation of PVC insulation. FTIR spectra further confirmed these findings by showing chemical changes such as dehydrochlorination and carbonyl group formation under high current stress. The MTTF values reflect the severity of these impacts, with samples exposed to higher currents showing drastically reduced lifespans. For instance, samples subjected to 100 A and 110 A currents exhibited MTTF values of 0.2 minutes and 0.004 minutes, respectively.